Importance of social principles of sovereign wealth funds - Jumaniyazov Inomjon To‘raevich; Abdullaev Aybek Nazarbaevich; Sabirov Mirza Qilichbayevich; Shavkat Bayramovich Babaev (Global Scientific Publishing, 2024)
Over the past three years, more and more sovereign wealth funds have been working to integrate environmental, social and governance (ESG) considerations into their investment processes. In 2021, 71% of sovereign wealth fund respondents said they had adopted an ESG approach compared to 24% in the previous year, according to the annual climate change survey administered by the International Forum of Sovereign Wealth Funds (IFSWF) and the One Planet Sovereign Wealth Funds network.1 2 This study offers three contributions to the understanding of how sovereign wealth funds are thinking about the social dimension
Keywords: sovereign wealth funds; ESG; environmental